ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE PERUSAHAAN TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2013) - Yoga Wira Atmaja (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2015)
The purpose of this study is to analyze the influence of institusional ownership,board of directors, audit committee, company size and leverage toward Cash FlowReturn On Assets (CFROA). The population is listed banking at Bursa Efek Indonesia(BEI) that chooses for 2009 until 2013 as the sample. The method of the research ispurposive sampling, there were 23 companies will be used as observation data.Analytical tool used is linier multiple regression analysis. Results show thatinstitutional ownership have not influence to cash flow return on assets. While board ofdirectors, audit committee, size firm and leverage have influence to cash flow return onassets.